Long-term Results of Arthroscopic Matrix-Assisted Autologous Chondrocyte Transplantation: A Prospective Follow-up at 15 Years. Issue 12 (October 2020) - Andriolo, Luca; Reale, Davide; Di Martino, Alessandro; De Filippis, Roberto; Sessa, Andrea; Zaffagnini, Stefano; Filardo, Giuseppe
Background: Matrix-assisted autologous chondrocyte transplantation (MACT) procedures have been developed to overcome some of the limits of first-generation autologous chondrocyte implantation. However, while good autologous chondrocyte implantation results have been documented over time, data are scarce on the long-term MACT results. Purpose: To evaluate long-term clinical results of a large cohort of patients treated with hyaluronic acid–based MACT for articular cartilage defects of the knee. Study Design: Case series; Level of evidence, 4. Methods: A long-term evaluation of 113 patients was performed (91 men, 22 women; mean ± SD age, 29.0 ± 10.6 years) for 115 knees affected by chondral and osteochondral lesions of the femoral condyles and trochlea. Of these, 61 knees had undergone previous surgery, while other procedures were combined during the same operation in 48 knees. These patients were prospectively evaluated before surgery and at 2, 5, and 10 years after surgery, as well as at a final mean follow-up of 15 years (range, 12-18 years), with various clinical scores: International Knee Documentation Committee (IKDC), EuroQol visual analog scale (EQ-VAS), and Tegner. Both surgical and clinical failures were documented. Results: The IKDC subjective score increased from the basal level of 39.9 ± 14.6 (mean ± SD) to 77.3 ± 20.5 ( P < .0005) at 2 years; results remained stable up to the 15-year follow-up (76.9 ± 20.5). EQ-VAS and Tegner scores showed a statistically significant improvement up to 10 years, with a further significant improvement at the final follow-up. A failure rate of 15.0% was documented, which increased to 21.7% when clinical failures were also considered. A worse outcome was found for older age ( P < .0005), female sex ( P = .002), degenerative lesions ( P < .0005), longer duration of symptoms ( P = .005), and previous surgery ( P < .0005). Conclusion: Arthroscopic MACT offered good and long-lasting results that were stable over time and resulted in a limited number of failures and reinterventions for up to 15 years of follow-up. Several factors were identified as having a prognostic value: a worse outcome could be expected in older patients, female patients, those affected by lesions with a degenerative cause, those having a longer duration of symptoms, and patients who underwent previous surgery.